preview files test - Olsson, Olof (Swedish National Data Service, 2025)
some test files and stuff

några testfiler
preview av filer test
Keywords: catering; catering; ECONOMICS; EKONOMI; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Geometry; Geometri; Computer graphics and computer vision; Datorgrafik och datorseende; Other Chemistry Topics; Annan kemi; Geophysics; Geofysik